Surrogacy in Islamic Jurisprudence and the Laws of the Arab Countries - layaida, Hadjer; Zekagh , Oussama (Journal of Neonatal Surgery, 2025)
Surrogacy is one of the latest developments, and despite its solution to the problems of infertility, it has great evils, such as spoiling the meaning of motherhood, exploiting it for trade, exploiting the poor class, and violating the five necessities that is conserving the offspring and honor, and falling into another problem is determining the true mother. The aim of the research is clarifying the various forms of artificial inoculation, and the identification of prohibited images, which are considered surrogacy among them, as well as determining the real mother, whether she is the mother with the oocyte owner, or the surrogate mother. The research then shows the extent to which the laws of the Arab countries formulate the issue of surrogacy, and despite their agreement to the prohibition, there is a deficiency in the codification, and some countries have not specified the criminal penalty for violating this order